Twenty-first workshop on geothermal reservoir engineering: Proceedings - United States. Department of Energy. Office of Energy Efficiency and Renewable Energy. (Stanford University, 1996)
PREFACE The Twenty-First Workshop on Geothermal Reservoir Engineering was held at the Holiday Inn, Palo Alto on January 22-24, 1996. There were one-hundred fifty-five registered participants. Participants came from twenty foreign countries: Argentina, Austria, Canada, Costa Rica, El Salvador, France, Iceland, Indonesia, Italy, Japan, Mexico, The Netherlands, New Zealand, Nicaragua, the Philippines, Romania, Russia, Switzerland, Turkey and the UK. The performance of many geothermal reservoirs outside the United States was described in several of the papers. Professor Roland N. Horne opened the meeting and welcomed visitors. The key note speaker was Marshall Reed, who gave a brief overview of the Department of Energy's current plan. Sixty-six papers were presented in the technical sessions of the workshop. Technical papers were organized into twenty sessions concerning: reservoir assessment, modeling, geology/geochemistry, fracture modeling hot dry rock, geoscience, low enthalpy, injection, well testing, drilling, adsorption and stimulation. Session chairmen were major contributors to the workshop, and we thank: Ben Barker, Bobbie Bishop-Gollan, Tom Box, Jim Combs, John Counsil, Sabodh Garg, Malcolm Grant, Marcel0 Lippmann, Jim Lovekin, John Pritchett, Marshall Reed, Joel Renner, Subir Sanyal, Mike Shook, Alfred Truesdell and Ken Williamson. Jim Lovekin gave the post-dinner speech at the banquet and highlighted the exciting developments in the geothermal field which are taking place worldwide. The Workshop was organized by the Stanford Geothermal Program faculty, staff, and graduate students. We wish to thank our students who operated the audiovisual equipment. Shaun D. Fitzgerald Program Manager.